A CRITIC-TOPSIS MCDM Technique under the Neutrosophic Environment with Application on Aircraft Selection (Contemporary Mathematics, 2023)
This paper develops a CRITIC-TOPSIS ''multi-criteria decision-making'' method under a neutrosophic environment. The neutrosophic set is a generalized version of the fuzzy and ''intuitionistic fuzzy set''. The purpose of this paper is the extension of the CRITIC-TOPSIS method using neutrosophic sets to create a more accurate and efficient decision support system for selecting a very light business jet (Bizjet). It provides the ranking to the selected number of Bizjets based on some pre-defined criteria under the neutrosophic CRITIC-TOPSIS method. The results of this study are obtained from the extended version of the previous study on decision-making for the selection of Bizjets. This study obtains results under the neutrosophic environment with a more realistic scenario.
Keywords: Neutrosophic set, CRITIC, TOPSIS, Multi-criteria decision-making